Nanocomposite films as electrochemical sensors for detection of catalase activity - Johnson, Dwight; Kim, Unyoung; Mobed-Miremadi, Maryam (Frontiers in Molecular Biosciences, 2022)
Cross-linked hydrogel substrates have garnered attention as they simultaneously enable oxidoreductase reactions in a control volume extended to adsorption of redox capacitors for amplification of electrochemical signals. In this study, the effect of catalase immobilization in mold-casted alginate-based thin films (1 mm × 6 mm × 10 mm) containing multi walled carbon nanotubes (MWCNT) coated with chitosan has been studied via amperometry. The amperometric response was measured as a function of peroxide concentration, at a fixed potential of −0.4 V vs. SPCE in phosphate-buffered saline (pH = 7.4). Results indicate substrate detection is not diffusion-limited by the 100 μm thick chitosan layer, if the cationic polyelectrolyte is in contact with the sensing carbon electrode, and the linear detection of the enzyme absent in solution is enabled by immobilization (R2 = 0.9615). The ferricyanide-mediated biosensor exhibited a sensitivity of 4.55 μA/mM for the optimal formulation at room temperature comparable to other nanomaterial hybrid sensing solution namely amine-functionalized graphene with an average response time of 5 s for the optimal formulation. The suitability of the optimized chitosan-coated alginate slabs nano-environment for co-encapsulation of catalase and carbon nanotubes was confirmed by cyclic voltammetry.